Adiabatic temperature change around coinciding first and second order magnetic transitions in Mn3Ga(C0.85N0.15) - Cakir, O.; Acet, M. (ELSEVIER SCIENCE BV, 2013)
The inverse magnetocaloric material in Mn3GaC relies on the presence of a first order antiferromagnetic-ferromagnetic transition at around 160 K. Since Mn3GaN is antiferromagnetic, the partial substitution of carbon by nitrogen in Mn3GaC enhances the antiferromagnetic exchange and shifts this transition to higher temperatures. At the Mn3Ga(C0.85N0.15) stoichiometry, the transition takes place at 180 K. The hysteresis at the transition reduces so that the inverse magnetocaloric effect is practically reversible. We study the magnetocaloric effect and the reversibility of the adiabatic temperature-change by magnetization and direct temperature-change measurements up to field-changes of 5 T. (C) 2013 Elsevier BY. All rights reserved.
Keywords: Magnetocaloric effect; Magnetic entropy; Adiabatic temperature change; Antiperovskite; ENTROPY CHANGE; FERROMAGNETIC TRANSITION; MN3GAC; DIFFRACTION; MANGANESE; Materials Science; Physics